Tropo de ser y haecceitas. Una interpretación de Alonso Briceño - José Tomás Alvarado Marambio (Síntesis. Revista de Filosofía, 2021)
Alonso Briceño, the first Chilean philosopher, contended that, for any x, the being of x = the haecceitas of x, and –further– that there is a ‘formal’ distinction between the being of x and the essence of x. In general, there is a ‘formal’ distinction between items z and v if and only if: (i) z  v, and (ii) z and v are mutually non-separable. It follows from these theses that ‘being’ should be taken to be a specific ontological component in particular objects and it is identical with the objects’ haecceitas. This is called here “the intuition of Briceño”. In this work it is considered the relevance that the intuition of Briceño might have for two of the most important theories about the nature of particular objects: the theories in which particular objects are constituted by a substratum and its properties, and the theories in which particular objects are bundles of tropes. It is argued that in both cases the intuition of Briceño, i. e. the idea that there is a specific trope of being in the particular object, brings important systematic advantages and, even more, it allows for a theoretical unification of both approaches usually considered as incompatible.